Perceptions of Young Adults Ages 18-25 Years Old Towards Unexpected Surge on Political Engagement During the 2022 National Election: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Citizens of the Philippines responded in a significant and diverse way to the 2022 nationalelection. Compared to previous elections in the Philippines, this election is extremely different.For young adults, different viewpoints and impressions regarding the choice of public leaderswere a serious issue. It also seems new and unusual because every citizen is becoming moreand more involved in politics. This phenomenon appeared without further research fromearlier studies. The researcher decided to investigate and look for answers from this study.This study follows all necessary health protocols and collects data via a semi-structuredinterview. The findings showed the perceptions of the seven respondents toward the 2022national election and how they were influenced and became aware of the situation during the2022 national election period, which is represented by their insights and experiences thatmostly overlap with each other. However, there were also perceptions that were freshlyintroduced by individual participants.Lastly, it aims to map out how these perceptions and experiences will improve thecommunity's ability to have an open conversation when it comes to politics and develop apeaceful election in the future. Moreover, three tables emerge from this study's findings,namely: (1) ENGAGEMENT: Awareness and Participation; (2) Perceptual Set Determinants;and (3) Factors Influencing Individual Behavior.
Keywords: Psychology